OPTIMALISASI HASIL BELAJAR KOGNITIF MELALUI PENGGUNAAN METODE SNOWBALL THROWING (Studi Kuantitatif pada Peserta Didik di Sekolah Dasar) - Meta Safitri; Ona Sastri Lumban Tobing; Rezkie Zulkarnain (Journal Education and Government Wiyata, 2025)
The research problem is the low learning outcomes of in Catholic Religious Education and Education subjects in Sanggau Regency Elementary Schools, particularly in the cognitive aspect. Previously, teachers used conventional methods, so this research will test the snowball-throwing to see its effect on student learning outcomes. The research method is a quantitative study with a pre-experimental research design, using one group pretest and post. Data collection techniques and tools used are test questions. The population consists of all class IV students of SDN 15 Nek Cikam, Sanggau, while the sample includes 12 Catholic class IV students. Data analysis techniques include normality testing, T-test, and Cohen's d-test. Based on data analysis, the average pretest result is 47.58 and the posttest average is 82, indicating an improvement in learning outcomes. This is supported by paired sample t-test results of 0.000, showing a significant difference in average learning outcomes before and after using the snowball-throwing, as the sig value (2-tailed) is 0.000 < 0.05, thus rejecting H0 accepting H1. The effect size test results are 2.489 large according Cohen d interpretation standards. Therefore, it is concluded that snowball-throwing method significantly optimizes student learning outcomes in the cognitive aspect, and it is hoped that this research will greatly contribute improving quality of learning in elementary schools.